Schizophrenia Recent Advances and Patient-Centered Treatment Perspectives - Yip, Jane (IntechOpen, 2023)
Patients with schizophrenia need a personalized medicine approach where the pharmacological and neurological mechanism is understood from the perspective of the patient's own experience and symptoms. Even though genetics play a role in the etiology, there are other important contributing risk factors. Schizophrenia is not a single-disease entity but has overlapping neurobiological and clinical profiles with other disorders such as autism and stress-related disorder. This expanded conceptualization benefits not only scholars but also diagnosing clinicians, as the diagnosis of schizophrenia is not always straightforward. The authors of this book discuss neurochemistry, animal models and antipsychotic models of schizophrenia to arrive at a personalized medicine approach for patients with schizophrenia. New treatment prospects from pharmacogenetic and neurotechnology research bring hope to clinicians and patients alike that, with continuing scientific studies, precisely targeted care is becoming available, with the potential of further alleviating the symptoms. Music therapy and patient-centered nursing practice are important aspects of clinical care as new directions are explored. This book will benefit researchers, clinicians, patients and family members needing a compact state-of-the-art reference resource. Knowledge is not only empowering but consoling, as our collective efforts to advance our understanding will translate into better treatment outcomes and the promise of a freer life for the patient.